STUDI TENTANG PATUNG SELAMAT DATANG DI DAERAH AIR TAWAR KOTA PADANG - TISA RIANTIKA, Dra. Lisa Wisdiarti, M.Sn., Yofita sandra, S.Pd., M.Pd. (Universitas Negeri Padang, 2017)
The purpose of this study was to describe the Welcome Statue at Air Tawar Area in Padang. This research is a descriptive qualitative research. Sources of data in this study of foam welcome statue (primary data), informants and literature(secondary data). Data collection procedures done through observation, interviews and documentation study. Based on the results of the study, concluded the following. The conclusions of the study: Welcome Statue at Air Tawar Area in Padang is asclupture that serve as icon that serves as a symbol of welcoming guests who enter the city of Padang, especially at Air Tawar area. Advice to future researchers to investigate further, so that the information about Welcome Statue at Air Tawar Area in Padang more complete.Keyword: welcome statue, foam, function